Transboundary Haze And General Aerosol Characteristic Over Pulau Pinang Using Aeronet And Modis Monitoring - Zahari, Mohamad Farid Izzat (2020)
2015 introduced Peninsular Malaysia with one of the worst recorded transboundary haze during the southwest monsoon period. Studies to identify and quantify the level of pollution have been done, but most are limited to year 2015 data only. This study aim to characterize the consequent year, 2016, mainly in terms of aerosol optical depth (AOD), identify any lingering effect of the subsequent haze, and assess the suitability of integrating MODIS AOD data with AERONET AOD data. The atmospheric properties of Pulau Pinang in terms of AOD, its Angstrom exponent (AE), and precipitable water (PW) were acquired. Using the 500 nm data as the main focus for the AOD parameters, anomalies in daily AOD reading were identified and investigated. Pre-monsoon season was found to have the highest mean AOD at 0.4879, followed by the northeast, southwest and post-monsoon season. The max AOD recorded was also during pre-monsoon season at 1.7788 and was associated with cloud contamination while the vice versa was observed during the post-monsoon season at 0.033 where downwashing of aerosol by constant rainfall was observed. Additionally, a peculiar series of spikes found in the pre-monsoon season was hypothesized to be the result of a transported aerosol mass from Bayan Lepas area. Aerosol type identification done using α–τ scatter plots for the 500 nm AOD and 440-870 nm AE found the dominant aerosol type were seasonally-dependant with the most dominant was BMA during the northeast and pre-monsoon season at 30% and 65%, followed by MA in the southwest and post-monsoon season at 33% and 75% respectively.